2021
DOI: 10.1016/j.jcmg.2020.10.023
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Pericardial Involvement in College Student Athletes Recovering From COVID-19

Abstract: Objectives We sought to explore the spectrum of cardiac abnormalities in student-athletes who returned to university campus in July 2020 with an uncomplicated Coronavirus disease 2019 (COVID-19). Background There is limited information regarding cardiovascular involvement in young individuals with mild or asymptomatic COVID-19. Methods Screening echocardiograms were performed in 54 consecutive student-athletes (mean age: 19 years, 85% males) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
290
3
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(322 citation statements)
references
References 32 publications
10
290
3
4
Order By: Relevance
“…Mean difference between patients with poor outcome and those without (a) and adjusted OR for each 1% decrease in LV-GLS. LV-GLS, left ventricular global longitudinal strain; OR, odds ratio severity of myopericardial damages, suggesting that regional longitudinal strain is an important marker, even in asymptomatic COVID-19 patients [28]. Croft et al study showed that there was no significant difference in terms of LV-GLS in non-survivors compared to survivors, this is likely due to the high prevalence of hypertension in the patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mean difference between patients with poor outcome and those without (a) and adjusted OR for each 1% decrease in LV-GLS. LV-GLS, left ventricular global longitudinal strain; OR, odds ratio severity of myopericardial damages, suggesting that regional longitudinal strain is an important marker, even in asymptomatic COVID-19 patients [28]. Croft et al study showed that there was no significant difference in terms of LV-GLS in non-survivors compared to survivors, this is likely due to the high prevalence of hypertension in the patients.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, reduced GLS might also be affected by acute conditions such as myopericardial damage and acute respiratory distress syndrome to other chronic causes (comorbidities) such as cardiovascular diseases, hypertension, and diabetes. A study noted that pericardial involvement was associated with lower GLS, in patients with COVID-19 [28]. Reduced GLS might be associated with the CAD coronary artery disease, CLD chronic lung disease, HF heart failure, NOS Newcastle Ottawa Scale Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In individualistic societies, this may be accomplished by de-emphasizing altruism and focusing on the individual cost-benefit. One way this may be achieved is by emphasizing the long-term morbidity costs (such as cryptic heart, lung, brain and kidney damage) as have been documented to occur in even asymptomatic COVID-19 patients in an age-independent manner (51)(52)(53). An additional approach is to provide an accurate and current picture of the risk of contracting the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of iJACC , Brito et al. ( 7 ) describe West Virginia University’s early experience with preparticipation cardiovascular screening during the COVID-19 pandemic. Among 160 student athletes returning to campus, 60 were found to have prior or active COVID-19 infection based on the results of PCR and/or IgG testing, among which 53 (37 symptomatic and 16 asymptomatic) completed further investigation to assess for myocardial and pericardial pathology.…”
mentioning
confidence: 99%
“…The authors of this paper ( 7 ) are to be commended, both for the foresight to study this important issue early in the course of the COVID-19 pandemic and for their transparent reporting of a comprehensive dataset. Results from this effort will contribute to the on-going dialogue about how to protect the health of competitive athletes infected with COVD-19 in several ways.…”
mentioning
confidence: 99%